Investigating Clustering Technique on Students’ Writing Skill in Narrative Text - Nindya Revani Anggitaningrum; Alimatun Alimatun; Hanafi Wibowo; Minkhatunnakhriyah Minkhatunnakhriyah; Albiansyah Albiansyah (Politeknik Negeri Padang, 2021)
Abstract— The purpose of this study was to explain the effect of clustering technique toward students’ writing skill of narrative text. This study used a quasi-experimental design with post-test only control group design. The population of this study was all students of tenth graders at SMA Tulus Bhakti Bekasi, with the amount of the students were 132 students. The samples of this research were taken by cluster random sampling consisting of 60 students. The students were divided into two classes, 30 experimental class (X IPS 1) and 30 other students in the control class (X IPS 2). The instrument used to collect data was learning achievement test in form of subjective test. The statistic method used to analyze the data was One-Way ANOVA using SPSS through the testing of Null Hypothesis. The result of ANOVA showed that value of sig (significance) is lower than 0.05 (0.000<0.05) or Fobserved with df (1/58) is higher than Ftable (28.185>4.01). Accordingly, the Null Hypothesis (Ho), stating that there is no effect of clustering technique on grade ten students’ writing skill of narrative text at SMA Tulus Bhakti, was rejected and the Alternative Hypothesis (Ha), stating that there is significant effect of clustering technique on grade ten students’ writing skill of narrative text at SMA Tulus Bhakti, was accepted. Based on the analysis of the data, the research has empirically proved that there is an effect of clustering technique has an effect on grade ten students’ writing skill of narrative text at SMA Tulus Bhakti Bekasi. Keywords— clustering techniques; quasi-experimental method; writing skill